Answer:
- 13
Step-by-step explanation:
Substitute x = - 1 into f(x) to obtain the remainder on dividing by (x + 1)
f(- 1) = - 2(- 1)³ - 4(- 1)² + 3(- 1) - 8
= 2 - 4 - 3 - 8 = - 13
Thus the remainder on dividing f(x) by (x + 1) is - 13
The formula to find<span> a </span>circle's area<span> (radius)</span>2<span> usually expressed as π ⋅ r 2 where r is the radius of a </span>circle<span>. </span>Area<span> of </span>Circle<span> Concept. The </span>area of a circle<span> is all the space inside a </span>circle's<span> circumference.</span>
Answer:
C. F(x) = (x+2)²
Step-by-step explanation:
A horizontal shift to the right by "h" units is achieved by replacing x with (x-h). The shift we want is to the left by 2 units, so h = -2, and we have ...
f(x) = g(x -(-2)) = g(x+2)
f(x) = (x+2)²
Answer:
b=14
Step-by-step explanation:
42 divided by 3 is 14
Answer:
![6y^1^6](https://tex.z-dn.net/?f=6y%5E1%5E6)
Step-by-step explanation:
I hope this has Helped :)